Difunctional vinyl sulfonate esters for the fabrication of tough methacrylate-based photopolymer networks. (5th December 2018) - Gorsche, Christian; Seidler, Konstanze; Harikrishna, Reghunathan; Kury, Markus; Koch, Thomas; Moszner, Norbert; Liska, Robert
Abstract: Chain transfer reagents serve as a valuable tool for the modification of methacrylate-based photopolymer networks. Employment of such chemistry enables easy tuning of mechanical and thermomechanical network properties, thus potentially widens the field of application for such crosslinked polymer networks. Thiols are the most prominent class of chain transfer reagents and possess a great number of favorable characteristics ( e.g., high conversion, reduced shrinkage stress, or high toughness, meaning the combination of high tensile strength and impact resistance). Mostly, thiols with higher functionality are used for network formation as monomer leaching and thinning effects are crucial drawbacks of monofunctional additives. Addition fragmentation chain transfer (AFCT) reagents ( e.g., vinyl sulfonate esters) have been recently introduced as powerful network regulators for methacrylate-based photopolymerization. After successful synthesis of a difunctional vinyl sulfonate ester the photoreactivity in methacrylate-based systems was compared to an equivalent thiol-ene system. Through the introduction of a difunctional vinyl sulfonate ester-derivative, homogeneous photopolymer networks with high conversions, reduced shrinkage stress, tunable crosslink density and thermomechanical properties were fabricated. The final materials exhibit high hardness, tensile strength and gel content as well as improved impact resistance. Graphical abstract: